Translation and validation of menopause quick 6 (MQ6) into the Malay language - Anusha Manoharan; Megat Muhammad Harris; Beh Hooi Chin; Koh Wen Ming; Zamzurina Asmuee; Norafini Salamon; Jerampang Pefer; H. Radhiyah; M. Nadia Hamimmah; Susan Goldstein; Shamala Ramasamy; Chandrashekhar T. Sreeramareddy (BMC Primary Care, 2024)
Abstract Background Inquiring conservative Asian women about their menopausal symptoms is often challenging in crowded primary healthcare clinics. Furthermore, the subject matter is culturally sensitive to most Malaysian women. Hence, the translation of the MQ6 into Malay is crucial to enable self-administration, eliminating the necessity for interviewers and mitigating potential respondent shyness. Methods The Menopause Quick 6 (MQ6) questionnaire was translated into the Malay language with an addition of an item, henceforth termed MQ6 (M). Forward and backward translation was performed. Face and content validity were conducted. MQ6 (M) was self-administered to 400 women aged between 40 and 60 attending six primary healthcare clinics in Malaysia. To ascertain the reliability for MQ6 (M), corrected Item-Total Correlation, Squared Multiple Correlation, Cronbach’s Alpha if the Item is Deleted, and Kuder-Richardson Reliability Coefficients (KR20). Exploratory factor analysis was done to determine its’ construct validity. Results The outcome of the validation was satisfactory. By the Lawshe method, the content validity ratios ranged from 0.6 to 1.0 and the content validity index was 0.914. The Internal consistency for the MQ6(M) Cronbach’s alpha was 0.711 while Kuder-Richardson Reliability Coefficients KR20 was 0.676. Factor loading of all four items is above 0.70, indicating a well-defined structure. Whereas factor loading for three items fell within the range of 0.50–0.69 indicating a practically significant threshold for a new questionnaire. Conclusion The MQ6 (M) has acceptable reliability and construct validity to be considered as a self-administered screening tool in primary care clinics in Malaysia.